Agnieszka Łoza, Paweł Beyga, Zaraza w Kościele, wyd. Leksem Studio, Żmigród 2021, ss. 169 - Ferdek, Bogdan (Poznańskie Studia Teologiczne, 2021)
In the opinion of Bogdan Ferdek, the new book of Agnieszka Łoza and Paweł Beyga is a special theological report on the state of the Church in Poland. During the pandemic time since 2021 the Catholic Church has had to search for solving problems in the Christian community. According to the authors of this new book, in the Polish Catholic Church two kinds of problems can be discovered. Firstly, there is a problem with morality among the clergy, the problems of sexual abuse and teaching the Catholic religion in Polish schools. Conversely, there is a problem related to the secularization of Polish people. Bogdan Ferdek in his review showed that the new book of two young Polish theologians is an answer to very important questions in the Polish Christendom in the time of the pandemic.